KESIAPSIAGAAN MASYARAKAT DALAM MENGHADAPI BENCANA TSUNAMI DI GAMPONG DAYAH MAMPLAM KECAMATAN LEUPUNG ACEH BESAR - Elviana, Meri; Desfandi, Mirza (Jurnal Pendidikan Geosfer, 2023)
ABSTRACTPreparedness is one of the efforts made to anticipate the possibility of a disaster occurring to avoid casualties, loss of property and changes in the life of the community in the future. Experts have found that tsunami disasters can repeat themselves and have cycles. This poses a serious threat to areas directly facing the ocean. Therefore, coastal communities must be vigilant and be able to adapt to their homes which are close to the coast. The purpose of this study was to find out how the community was prepared to face the tsunami disaster in Dayah Mamplam Village, Leupung District, Aceh Besar District. This study uses a quantitative approach with a survey method. The population in this study was the Gampong Dayah Mamplam community, which amounted to 200 families with 736 people and took a sample of 20% of the total heads of families so that there were 40 families as research samples. Based on the results of research and discussion, it can be concluded that the level of preparedness of the Gampong community Dayah Mamplam, Leupung District, Aceh Besar District in facing the tsunami disaster as a whole is in the almost ready category with an index of 56.36. The highest index is in the knowledge parameter with a total of 61.89, while the disaster ranking which has the lowest index of the four parameters is resource mobilization with a total of 42.88.Keywords: Preparedness, Tsunami Disaster